Chondroitin sulfate immobilization at the surface of electrospun nanofiber meshes for cartilage tissue regeneration approaches - Piai, Juliana Francis (2017)
Aiming at improving the biocompatibility of biomaterial scaffolds, surface modification presents a way to preserve their mechanical properties and to improve the surface bioactivity. In this work, chondroitin sulfate (CS) was immobilized at the surface of electrospun poly(caprolactone) nanofiber meshes (PCL NFMs), previously functionalized by UV/O3 exposure and aminolysis. Contact angle, SEM, optical profilometry, FTIR, X-ray photoelectron spectroscopy techniques confirmed the success of CS-immobilization in PCL NFMs. Furthermore, CS-immobilized PCL NFMs showed lower roughness and higher hydrophilicity than the samples without CS. Human articular chondrocytes (hACs) were cultured on electrospun PCL NFMs with or without CS immobilization. It was observed that hACs proliferated through the entire time course of the experiment in both types of nanofibrous scaffolds, as well as for the production of glycosaminoglycans. Quantitative-PCR results demonstrated over-expression of cartilage-related genes such as Aggrecan, Collagen type II, COMP and Sox9 on both types of nanofibrous scaffolds. Morphological observations from SEM and LSCM revealed that hACs maintained their characteristic round shape and cellular agglomeration exclusively on PCL NFMs with CS immobilization. In conclusion, CS immobilization at the surface of PCL NFMs was achieved successfully and provides a valid platform enabling further surface functionalization methods in scaffolds to be developed for cartilage tissue engineering.